Gender differences in smallholders' socioeconomic networks and acquisition of seed of improved wheat varieties in Ethiopia - Jaleta, Moti; Euler, Michael; Gartaula, Hom Nath; Krishna, Vijesh (Frontiers Media, 2022)
Enhancing farmers' access to improved seeds is essential to increase productivity and ensure food security in the Global South. However, for many socially marginalized groups, seed access is constrained by the weak institutions governing the input supply chains and the dissemination of information. Using cross-sectional survey data collected from 1,088 farming households in three major wheat-growing regional states of Ethiopia in 2021, this paper assesses empirically how participation in different socioeconomic institutions by men and women farmers shapes their access to and acquisition of seed of improved wheat varieties. The results show that the seed market in the study area is largely informal, where the recycling of wheat seeds from the previous season is a common practice among both male- and female-headed households. However, a significant difference exists between male- and female-headed households regarding patterns of varietal use, with male farmers growing newer wheat varieties more frequently. Men are also more active than women in local social and economic institutions, and their participation is positively associated with the adoption of new wheat varieties. Thus, strengthening the local social and economic institutions and supporting equitable participation of both male- and female-headed households in these institutions could facilitate the diffusion of quality seeds of improved and recently released wheat varieties in countries where the informal seed system plays a major role in seed acquisition.